Parallel auditing of the University of Oxford and the University of Cambridge’s institutional repositories - Halvarsson, E; Mason, SA; Pretlove, L; Langley, S (2017)
The Polonsky Digital Preservation at Oxford and Cambridge Project (DPOC) is a collaboration between Bodleian Libraries and Cambridge University Library with funding from the Polonsky Foundation. The project will enhance the libraries’ digital preservation programmes by drawing upon existing expertise and research in the fields of digital preservation and digital curation. This poster is about the auditing activities at both institutional repositories to understand their current digital preservation landscape.